Integrated Biotechnology Management of Biosolids: Sustainable Ways to Produce Value—Added Products - Vaithyanathan, Vasanth Kumar; Cabana, Hubert (Frontiers in Water, 2021)
Biosolids (BS) are organic dry matter produced from wastewater treatment plants (WWTPs). The current yearly worldwide production of BS is estimated to be around 100-125 million tonnes and is expected to continuously increase to around 150-200 million tonnes by 2025. Wastewater treatment industries across the globe strive to achieve a green and sustainable manufacturing base for the management of enormous amounts of municipal BS, which are rich in nutrients and organic dry matter along with contaminants. The management of these organic-rich wastes through environmentally friendly recovery technologies is a major challenge. The need to improve waste biomass disposal by biological development and develop more economically viable processes has led to a focus on the transformation of waste resources into value-added products (VAP). This paper assesses the leading disposal methods (based on volume and contaminant reduction) and reviews the state of biotechnological processes for VAP recovery from municipal wastewater sludge (untreated solid waste residual) and BS (stabilized solid waste which meets criteria for its use in land). A review of the anaerobic and aerobic digestion processes is presented to provide a holistic overview of this growing research field. Furthermore, the paper also sheds light on the pollutant reduction and resource recovery approaches for enzymes, bioflocculants, bioplastics, biopesticides, and biogas as a mean to represent BS as a potential opportunity for WWTPs. However, only a few technologies have been implemented for VAP resource recovery and a shift from WWTPs to waste resource recovery facilities is still far from being achieved.